KAJIAN YURIDIS TERHADAP UNDANG-UNDANG NO. 19 TAHUN 2004 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NO. 1 TAHUN 2004 - Jamilus, - (E-Journal Widya Yustisia, 2018)
The birth of the regulation No. 1 in 2004 which became Act No. 19 of 2004 led to a wide rejection by people in various areas mining and at the national level. The rejection at the national level is done by various non-governmental Organizations Coalition who joined in the rescue of protected forest Advocacy Team by doing a petition for annulment of law 19/2004 through judicial review to the Constitutional Court, arguing in a regulation is still on the run, the impact would cause bad for society around the mine. The purpose of this paper to discuss: (1) whether law No. 19 of 2004 warranties are material to the legal rights of citizens in order to honour, the fulfillment of human rights in the field of natural resource management and environment (2) whether law No. 19 of 2004 in line with the law reform in the field of natural resource management and the environment as well as the social and economic impact, (3) the impact of law 19/2004 for the community. The method used is the normative approach, data obtained from the research libraries. The results of the study indicate that: (1) determination of the regulation No. 1/2004 are considered to be weak and not in accordance with the provisions of article 22, paragraph (1) of the Constitution, (2) the substance of the arrangements of the mining licence less precise products is set out in the legislation because of the nature of the agreement and permission was temporary. (3) the impact of the community will cut off the economic value of ecological and environmental capital, and give rise to numerous conflicts experienced by the community. Need for harmonization with basing on scientific studies which can be objectively justified.